Improved Electrochemical Performance of Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2 Cathode Material Synthesized by the Polyvinyl Alcohol Auxiliary Sol-Gel Process for Lithium-Ion Batteries. (10th December 2018) - Wang, He; Chang, Mingning; Zheng, Yonglei; Li, Ningning; Chen, Siheng; Wan, Yong; Yuan, Feng; Shao, Weiquan; Xu, Sheng
Abstract : A lithium-rich manganese-based cathode material, Li1.25 Ni0.2 Co0.333 Fe0.133 Mn0.333 O2, was prepared using a polyvinyl alcohol (PVA)-auxiliary sol-gel process using MnO2 as a template. The effect of the PVA content (0.0–15.0 wt%) on the electrochemical properties and morphology of Li1.25 Ni0.2 Co0.333 Fe0.133 Mn0.333 O2 was investigated. Analysis of Li1.25 Ni0.2 Co0.333 Fe0.133 Mn0.333 O2 X-ray diffraction patterns by RIETAN-FP program confirmed the layered α -NaFeO2 structure. The discharge capacity and coulombic efficiency of Li1.25 Ni0.2 Co0.333 Fe0.133 Mn0.333 O2 in the first cycle were improved with increasing PVA content. In particular, the best material reached a first discharge capacity of 206.0 mAhg −1 and best rate capability (74.8 mAhg −1 at 5 C). Meanwhile, the highest capacity retention was 87.7% for 50 cycles. Finally, electrochemical impedance spectroscopy shows that as the PVA content increases, the charge-transfer resistance decreases.